Case reportHighly elevated levels of the antigen Ca-125 associated with inflammatory abdominal masses - Wilczak, Maciej; Rzymski, Paweł; Stryjakowska, Ksenia; Stanek, Robert; Opala, Tomasz (Archives of Medical Science, 2007)
CA-125 is well known as an ovarian cancer marker. Various studies have noted it’s growth in benign gynecologic conditions. A young woman was presented with an abdominal discomfort associated with pelvic masses and a very high level of CA-125=1259.85 U/mL. Surgical treatment revealed an inflammatory tumour. After excision of the masses CA-125 antigen decreased to the normal value. Very high levels of CA-125 are not necessarily associated with malignant process.